Feminisms in Canadian Educational Contexts: A Literature Review - Heather Syme Anderson (Canadian Society for Studies in Education, 2016)
Feminism is a theory used to explain the phenomenon of gender inequality, and is particularly useful for researchers working in education, since gender inequity continues to be a pressing issue in educational contexts. The aim of this literature review is to clarify four feminist conceptualizations of gender inequality (liberal feminist, socialist feminist, radical feminist, and queer theory) to show how these are operationalized differently in educational contexts. These four conceptualizations of gender inequality are situated within three epistemological categories of feminist theorizing: a) feminist empiricism, b) feminist standpoint, and c) postmodern feminism. By understanding the distinctions between various feminist theories on gender inequality, researchers and practitioners can use these distinctions to interpret historical and current educational efforts towards gender equity. Further, educators and policymakers can also use these understandings to develop more nuanced approaches to gender equity.